Factors associated with breast self-examination among Malaysian women teachers - Parsa, Parisa; Kandiah, Mirnalini; Parsa, Nakisa (World Health Organization, 2011)
The purpose of this study was to examine factors related to breast self-examination (BSE) among teachers in Selangor, Malaysia. A cross-sectional study was conducted among 425 female teachers in 20 randomly selected secondary schools. A self-administered questionnaire based on the health belief model was randomly selected secondary schools. A self-administered questionnaire based on the health belief model was used, including sociodemographic background and knowledge, beliefs and practices about breast cancer and BSE. Only 19% of the women performed BSE on a regular basis. Higher knowledge about breast cancer, greater confidence in performing BSE and regular visits to a physician were significant predictors for practising BSE. To promote BSE practice among Malaysian women, tailored health education and health promotion programmes should be developed based on a specific understanding of women's health beliefs.